Evaluación de adaptabilidad de clones de cacao (Theobroma cacao L.), utilizando Lluvia sólida en el cantón Caluma, provincia Bolívar. - Cruz Ycaza, Tamara Pensilvania (2020)
World cocoa production exceeds 4,000,000 MT of grain. In Ecuador, cocoa production is a very important item, generating significant sources of economic income. In the canton Caluma there are 4770 hectares planted, which, if applied, will be able to supply local, national and regional markets. Solid rain is a technology whose main component is the polyacrylate potassium polymer, which allows gelatinizing the liquids and rehydrating them repeatedly during their useful life. The objectives of this research were: To determine the best dose of solid rain in the development of cocoa clones. Establish the economic costs of the different doses of solid rain. The present trial was developed in the Lomas de Pita sector, Caluma canton, Bolívar province. 243 cacao plants were used: A1: 81 plants of Pichilingue Aromatic EETP-800, A2: 81 plants of Pichilingue Fine EETP-801, A3: 81 plants of CCN 51. Three doses of solid rain: B1: 0 grams per plant, B2: 36 grams per plant, B3: 54 grams per plant. In the statistical analysis, the following were evaluated: Tukey test at 5% for Factor A, Factor B and for interactions A x B, when Fisher's test was significant. Contrasts orthogonal comparisons: Aroma Pichilingue EETP-800 vs. Fine Pichilingue EETP-801; Aroma Pichilingue EETP-800 vs. CCN-51; Fine Pichilingue EETP-801 vs. CCN-51. Correlation analysis and simple linear regression. Based on the statistical results we infer that the development of the cocoa clones is not the same with the doses of solid rain, therefore we reject the null hypothesis and accept the alternative hypothesis. It is concluded: The development of the three cocoa clones was similar. The use of solid rain allowed to maintain humidity levels in the soil that favored the good phenological development of the crop. For the Caluma agroecological zone and at the time of the transplant carried out (July 1), a greater vigor was evident in B3: 54 grams. It is economically profitable to use solid rain in doses of 54 grams per plant as a water reservoir, making it possible to transplant cocoa in dry months, being $ 11.61 cheaper than without applying solid rain.